The improving of effectiveness school-based enterprise: A structural equation modeling in vocational school management - Arie Wibowo Khurniawan; Illah Sailah; Pudji Muljono; Bambang Indriyanto; M. Syamsul Maarif (Institute of Advanced Engineering and Science, 2021)
The study aimed to investigate the influence of total quality management and school governance on school management effectiveness, whether school governance as an antecedent of total quality management and school management effectiveness. The object of research is the vocational high school with the Regional Public Service Agency status (school-based enterprise) in Indonesia. The research is a quantitative research with survey method. The sample of 533 people who are school principals, teachers, and students. It was selected by proportional stratified random sampling. The data analysis using structural equation modeling (SEM). The research finding is the total quality management has a significant influence on school management effectiveness. The mediation analysis indicates that school governance as the antecedent of total quality management and school management effectiveness. The improvement of effectiveness school-based enterprises should consider implementing total quality management and it will be increasingly by school governance application. The modeling that correlates total quality management and school governance to improved vocational school management effectiveness, especially at vocational school with Regional Public Service Agency status (school-based enterprise).